A proteomics analysis of neointima formation on decellularized vascular grafts reveals regenerative alterations in protein signature running head: Proteomics analysis of neointima formation - Chen, Chunyang; Lu, Ting; Wu, Zhongshi; Xie, Xinlong; Liu, Yalin; Huang, Can; Liu, Yuhong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Neointima formation contributes to vascular grafts stenosis and thrombosis. It is a complex reaction that plays a significant role in the performance of vascular substitutes. Despite its critical implications, little is known about mechanisms underlying among the neointima formation. This study compares neointima proteome in different stages and plasma samples. Methods: Heterogenous acellular native artery were implanted as abdominal aortic interposition grafts implanted in a rabbit model. Grafts were harvested 0.5, 1, 4, 6, 7, 14, 21 and 28days post-surgery for histological and proteomic analysis of the neointima. Results: Histological examination showed a transformed morphological pattern and components, including serum proteins, inflammatory cells and regenerative cells. Proteomics analysis of the neointima indicated distinct characteristics after 14 days implantation compared with early time points. Early changes in the neointima samples were proteins involved in acute inflammation and thrombosis, followed by the accumulation of ECM proteins. A total of 110 proteins were found to be differentially expressed in neointima with in later samples compared with early controls. The enriched pathways were mainly protein digestion and adsorption, focal adhesion, PI3K-Akt signaling pathway and ECM-receptor interaction in the late stage. All distributions of proteins in the neointima are different compared to plasma. Conclusions: The biological processes of neointima formation at different time points identified with proteome found that development characteristics of vascular structure on a decellularized small vascular graft, and significant differences were identified by proteomics in late-stage neointima after implantation, most notably an upregulation of ECM components. The present study demonstrates an interaction between biological matter and vascular graft, and provides insights into the neointima biological process changes and facilitates the construction of a functional bioengineered small vascular graft for future clinical applications.